Konsentrasi Industri Perdagangan Beras Eceran Dikecamatan Panjang Dan Faktor-Faktor Yang Mempengaruhinya - Mela Nopita Sari; Emi Maimunah (Departement of Mathematics Education, 2023)
This study aims to find out how big the level of concentration and the factors that influence it in the retail rice trading industry in Panjang District, Bandar Lampung City in 2022. The analytical method used in this study is the correlation significance test method. Meanwhile, to measure the concentration level, the Market Share Index, Concentration Index, and Hafindhal Index are used. The dependent variable used in this study is the level of concentration of retail rice trading in Panjang District and the independent variables include the amount of sales, business strategy, and capital. The results of this study indicate that the amount of sales and capital has a positive and significant relationship to the level of concentration of retail rice trade in Panjang District, while the business strategy variable has a positive but not significant relationship to the level of concentration of retail rice trade in Panjang District.